2020
DOI: 10.3390/ijms21041200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Profiling Illuminates the Fruitlet Abscission Mechanism of Sweet Cherry as Induced by Embryo Abortion

Abstract: Sweet cherry (Prunus avium L.) is a delicious nutrient-rich fruit widely cultivated in countries such as China, America, Chile, and Italy. However, the yield often drops severely due to the frequently-abnormal fruitlet abscission, and few studies on the metabolism during its ripening process at the proteomic level have been executed so far. To get a better understanding regarding the sweet cherry abscission mechanism, proteomic analysis between the abscising carpopodium and non-abscising carpopodium of sweet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…In recent research, the genes of cellulase, pectinase, polygalacturonase, expansin, xyloglucan endotransglucosylase/hydrolase, and peroxidase were found to be signi cantly up-regulated in the abscising carpopodium. In addition, previous proteomic studies have also shown the same results [49]. These results suggested that the remodeling of cell walls might promote the sweet cherry fruitlet shedding.…”
Section: Cell Wall Remodeling Implicates In Fruitlet Abscission Of Swsupporting
confidence: 73%
See 1 more Smart Citation
“…In recent research, the genes of cellulase, pectinase, polygalacturonase, expansin, xyloglucan endotransglucosylase/hydrolase, and peroxidase were found to be signi cantly up-regulated in the abscising carpopodium. In addition, previous proteomic studies have also shown the same results [49]. These results suggested that the remodeling of cell walls might promote the sweet cherry fruitlet shedding.…”
Section: Cell Wall Remodeling Implicates In Fruitlet Abscission Of Swsupporting
confidence: 73%
“…This result implies that the formation of plant cells is hindered, which in turn leads to programmed cell death and the shedding of plant organs. In addition, the proteomics at the early stage of this research group also showed that a close relationship existed between the cytoskeleton and the shedding of sweet cherry fruit [49].…”
Section: The Cytoskeleton Regulate Fruitlet Abscission Of Sweet Cherrymentioning
confidence: 70%
“…In addition to angiosperms, RGFs have been suggested to be present in the lycophyte S. moellendorffii (Ghorbani et al, 2015). RGFs can signal through RGF RECEPTOR (RGFR)/ROOT GROWTH FACTOR INSENSITIVE (RGI) receptors, which were discovered a few years ago (Shinohara et al, 2016; Song et al, 2016; Qiu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A double mutant of the closely related receptors HAE and HSL2 was needed to disclose their involvement in floral organ abscission, like their peptide ligand IDA (Butenko et al, 2003; Cho et al, 2008; Stenvik et al, 2008). Furthermore, triple to quintuple mutants were necessary to disclose the involvement of the RGI receptors in root development, with RGFs peptides as ligands (Shinohara et al, 2016; Song et al, 2016; Qiu et al, 2020). Thus, functional redundancy on the receptor side as well as the peptide side has made it complicated to identify ligand-receptor pairs through genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Olivares-García et al [ 22 ] suggested that in the embryogenic culture of avocados, there is an enhanced phenylpropanoid metabolism for the production of the building blocks of lignin having a role in cell wall reinforcement for tolerating stress response. Qiu et al [ 23 ] indicated that embryo abortion might lead to phytohormone synthesis disorder, which effected signal transduction pathways, and hereby controlled genes involved in cell wall degradation and then caused the abscission of fruitlets in sweet cherry trees. Wu et al [ 24 ] revealed by using iTRAQ that plastid pigment metabolism contributes to leaf color changes in Nicotiana tabacum during curing.…”
mentioning
confidence: 99%